Post Abortion Care with Misoprostol – A Step towards Reduction of Surgical Interventions (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Treatment with misoprostol as per protocol is becoming widely recognized as a low cost and easy to use means of uterine evacuation. In contrast, post abortion care (PAC) with Dilatation evacuation and curettage (D, E & C), Manual Vacuum Aspiration (MVA) are costly and complicated procedures specially in inexperienced hands.Objective: To see the outcome of the patients treated with misoprostol as per the guideline.Materials and Methods: This prospective study was carried out at CMH Momenshahi from October 2016 to March 2017. 50 patients with 1st trimester abortion was selected, treated with directly observed doses of misoprostol. For incomplete abortion 600μgm orally, for missed abortion and blighted ovum 600 μgm sublingually, 3 hourly 3 doses. Then followed up after 7 days with an USG of pelvic organs report. Data was collected, processing was done using SPSS version 20.Results: Among 50 patients 10 were primigravida, 40 were multigravida. Their age ranged from 20-38 years. 11 had previous miscarriages. Gestational age ranged from 5-12 week. Symptoms were vaginal bleeding in 23, pain abdomen in 15 and both in 12 patients. 28 patients needed parenteral analgesia. Expulsion of product of conception occurred from 30 minutes to 96 hrs after administration of last dose. Surgical evacuation was done in 15 (30%) patients. Indications were excessive P/V bleeding and retained product of conception. Emergency curettage for bleeding was done in 4 patients. 5 patients needed readmission. All 50 patients attended after 7 days.Conclusion: Management of 1st trimester abortion with misoprostol as per guideline is highly satisfactory. But it requires patience, effective counselling and follow up. If we can follow these, we can reduce surgical interventions and its complications considerably.JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 39-41